(7a+2)-(2a-4)=65a

Simple and best practice solution for (7a+2)-(2a-4)=65a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7a+2)-(2a-4)=65a equation:



(7a+2)-(2a-4)=65a
We move all terms to the left:
(7a+2)-(2a-4)-(65a)=0
We add all the numbers together, and all the variables
-65a+(7a+2)-(2a-4)=0
We get rid of parentheses
-65a+7a-2a+2+4=0
We add all the numbers together, and all the variables
-60a+6=0
We move all terms containing a to the left, all other terms to the right
-60a=-6
a=-6/-60
a=1/10

See similar equations:

| n=((6-5n)((6-5n)+1))/2 | | 2(7z-7)=2(7z−7)=14 | | −6+5y=−3(2−y) | | -5.3w+8.0w-11.6=14-25.6+2.7w | | 2+n=-7n+7n | | 1/7x−2=11 | | 6+6v=30 | | 0.25z=1.25z | | −20=−0.2k | | h=2.5(11)+60.3 | | 2x+3=3(x=7) | | −17/18+p=1/9 | | 8x−6=34 | | 3q+8=2q-17 | | 20+5t=-5t | | B. 45y=445 C. 8y=48 D. 3.2+y=9 E. y÷4=24 | | w/5-16=3 | | 9x=5x-1 | | 20p+16=16p | | 7x+7=−77 | | -16-19k=-18k | | 5x+4x-3+7=40 | | 84.8=8(m+2.7) | | 20*y=-40 | | -20t+4−13=-10−20t | | x-2.3=0.09 | | 4q−8=4q−3 | | 4*y=-8 | | 6x−5=31 | | 75=99+2s | | p−15=1 | | -7m+16=-8m-m |

Equations solver categories